Kemampuan literasi dalam pembelajaran membaca teks pada siswa kelas IV SD melalui e-modul - Anita Rahmawati (COLLASE (Creative of Learning Students Elementary Education), 2023)
A successful learning process requires appropriate teaching materials. Without learning media, teachers will certainly experience difficulties in improving the quality of their learning. Thus, learning media is very important to develop so that the quality of learning improves. This study aims to determine the effectiveness of using e-modules to improve literacy skills in reading texts in class IV students at SDN 2 Brantaksekarjati Welahan Jepara in the 2022/2023 academic year with a total of 15 students. This type of research is descriptive qualitative. The results of this study are the effectiveness of the use of e-modules based on the average percentage of observations of 92.25%, and student responses to the use of e-modules of 89.33% with very effective criteria. Furthermore, 92% of students obtained mastery of the learning outcomes test.Keywords: Learning Media, E-Module, Reading Reading Texts